(Re-)Sources of innovation. Understanding and comparing innovation dynamics through the lens of communities of practice. - Müller, Felix C.; Ibert, Oliver (My University, 2014)
Communities of practice play an important role in innovation processes. It is however still unclear what their particular function is. One problem is that the concept seems to be too wide and too narrow at the same time to address this question adequately. The notion is too narrow as long as it remains focused on its original understanding of craft - based practices of knowing. The notion however is too wide to encompass the whole multiplicity of knowledge practices that meanwhile have evolved in knowledge societies. In this paper we develop further a typology that has been proposed by Amin and Roberts some year s ago. We complement their inductive approach with deductive elements. Concretely, we introduce the systematic dimensions domain s of knowing (scientific vs. socio - cultural knowing) and modes of reflexivity (push vs. pull) to establish a matrix to locate different types of communities of practice. This matrix provides a useful template to study the influences of communities of practice on innovation processes in a comparative way. These types of communities can be regarded as distinct sources of innovation, as a locus in which novel ideas emerge and subsequently take particular trajectories. Moreover, these types of communities provide distinctive resources for innovation that can be used at different phases of an innovation process to complete decisive steps.
Keywords: Information; Wissenschaft; Forschung; Innovation; Wissenschaft und Forschung; Innovationsforschung; Wissensökonomie; Wissensmanagement; Innovationsprozess; Organisationsforschung; Lernende Organisation; Forschungsprozess; Wissenschaftsstandort